2023
DOI: 10.20448/jeelr.v10i2.4432
|View full text |Cite
|
Sign up to set email alerts
|

Designing gamification for case and project-based online learning: A study in higher education

Abstract: The emergence of online learning has become important during the COVID -19 pandemic due to the advent of internet technology. The unpreparedness of planning and implementing online learning has caused many problems during the pandemic such as limited or monotonous academic materials as well as difficulty in organizing activities and student involvement. Online learning is also more stressful because students are stuck in private academic processes in the absence of challenging and fun activities leading to kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Participants positively perceived PjBL, recognizing its potential to enhance critical thinking, collaboration, and deeper understanding of course material. This aligns with previous research (Abuhmaid et al, 2020;Crawford et al, 2024;Cruz et al, 2023;Plews et al, 2024;Şahin & Kılıç, 2024;Suartama et al, 2023) highlighting the effectiveness of PjBL in promoting active learning and skill development in the classroom. However, the study also identified several challenges and areas for improvement in implementing PjBL in online courses.…”
Section: Findings and Discussionsupporting
confidence: 90%
“…Participants positively perceived PjBL, recognizing its potential to enhance critical thinking, collaboration, and deeper understanding of course material. This aligns with previous research (Abuhmaid et al, 2020;Crawford et al, 2024;Cruz et al, 2023;Plews et al, 2024;Şahin & Kılıç, 2024;Suartama et al, 2023) highlighting the effectiveness of PjBL in promoting active learning and skill development in the classroom. However, the study also identified several challenges and areas for improvement in implementing PjBL in online courses.…”
Section: Findings and Discussionsupporting
confidence: 90%
“…Furthermore, research has identified various models and frameworks for designing and implementing PjBL, such as the Buck Institute for Education's (BIE) Gold Standard PBL model and the framework proposed by Thomas in Wijnia (Wijnia et al, 2024). These models emphasize essential elements of effective PjBL, including authentic challenges, student autonomy, inquiry and investigation, and public presentation of learning outcomes (do Amaral et al, 2023;Suartama et al, 2023). Despite the wealth of research on PjBL, there is a notable gap in understanding the role of teachers in effectively facilitating this instructional approach.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding of students is very important, namely, among others, their hopes and goals in participating in e-learning, speed in accessing the internet, costs for internet access, as well as background knowledge regarding readiness to participate in learning. (Suartama, 2014) Zoom cloud meeting is a video and audio-based communication application via the internet network. Learning media through the zoom application This meeting is more dominantly used by students in e-learning learning where this application is very useful in the distance teaching and learning process, making it easier for educators to interact with their students, so that this application supports e-learning based learning.…”
Section: Introductionmentioning
confidence: 99%